1997
DOI: 10.1023/a:1018811210175
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Oxygen free radicals (OFR) are implicated in the pathogenesis of stress, chemically induced gastric lesions, and gastrointestinal injury. The concentration-dependent scavenging abilities of bismuth subsalicylate (SBS), colloidal bismuth subcitrate (CBS), and selected OFR scavengers, including superoxide dismutase (SOD), catalase, mannitol, and allopurinol were examined against biochemically or chemically generated superoxide anion, hydroxyl radical, and hypochlorite radical plus hypochlorous acid based on a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…These findings were unexpected, as we and other investigators have demonstrated that a low zinc status is associated to a condition of oxidative stress (9,10,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). NF-B is recognized to be activated by different oxidant species, by conditions that induce the intracellular production of oxidants and by oxidative-degradation products (35-38).…”
Section: Discussionmentioning
confidence: 91%
“…These findings were unexpected, as we and other investigators have demonstrated that a low zinc status is associated to a condition of oxidative stress (9,10,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). NF-B is recognized to be activated by different oxidant species, by conditions that induce the intracellular production of oxidants and by oxidative-degradation products (35-38).…”
Section: Discussionmentioning
confidence: 91%
“…DNA fragmentation in control samples is expressed as percentage of total DNA appearing in the supernatant fraction. Treatment effects are reported as percent of control fragmentation [22].…”
Section: Assessment Of Dna Fragmentationmentioning
confidence: 99%
“…Accordingly, the proanthocyanidins in grape seed extracts have been suspected to have free-radical scavenging abilities and to decrease the susceptibility of healthy cells to toxic and carcinogenic agents [48][49][50]. Analogously, in vitro and in vivo studies have demonstrated that these compounds exhibit the ability to scavenge reactive oxygen and nitrogen species [51], as well as inhibiting the progression of arteriosclerosis and preventing the increase of LDL cholesterol in high-cholesterol-fed rats [52].…”
Section: Biological Activity Of Catechins and Proanthocyanidins Othermentioning
confidence: 99%